IMPLIKASI SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM (Studi Kasus di MAN 1 Polewali Mandar) - Naslim, Naslim; Mulyadi, Mulyadi; Mulyono, Mulyono (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: Implications of Academic Supervision of Head of Madrasah in Improving Professional Islamic Religious Education Teachers (Case Study at MAN 1 Polewali Mandar) This study aims to describe and analyze the implications of the academic supervision of the madrasah principal on improving the professionalism of PAI teachers at MAN 1 Polewali Mandar. The approach in this study uses a qualitative approach to the type of case study. The object of this research is the supervision program. In this study, data was obtained from the head of the madrasa, deputy head of the madrasa in the field of curriculum, and Islamic religious education teachers using data collection techniques, namely in-depth interviews, observation, and documentation. Data analysis efforts are carried out by reducing data, presenting data, and verifying data. The effort to check the validity of the data is done by using a triangulation technique. The results of the study found that: (1) Through the academic supervision program by the madrasah principal, it shows positive and significant things in improving teacher professionalism to assist teachers in developing their competence in planning, implementing, and evaluating learning. (2) The existence of teacher work motivation by the madrasah principal becomes the teacher's strength to have a strong desire to carry out work with high enthusiasm, so the effort to improve teacher professional competence is to increase teacher work motivation so as to improve teacher professional competence. (3) Through an academic supervision program by the head of the madrasah, teachers are made more professional at teaching, so that students are enthusiastic about taking part in learning because of the teacher's ability to master learning materials and be able to liven up the learning atmosphere. Teachers who have professional competence will also have implications for student learning to achieve. Abstrak: Implikasi Supervisi Akademik Kepala Madrasah dalam Meningkatkan Profesional Guru PAI (Studi Kasus di MAN 1 Polewali Mandar) Penelitian ini bertujuan mendeskripsikan dan menganalisis implikasi supervisi akademik kepala madrasah dalam meningkatkan profesional guru PAI di MAN 1 Polewali Mandar. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Adapun objek pada penelitian ini mengenai program supervisi. Dalam penelitian ini, data diperoleh dari kepala madrasah, wakil kepala madrasah bidang kurikulum, dan guru pendidikan agama Islam dengan menggunakan teknik pengumpulan data yaitu wawancara mendalam, observasi, dan dokumentasi. Upaya analisis data dilakukan dengan cara mereduksi data, menyajikan data, dan memverifikasi data. Adapun upaya untuk mengecek keabsahan data dilakukan dengan teknik triangulasi. Hasil penelitian menemukan bahwa: (1) Melalui program supervisi akademik oleh kepala madrasah menunjukkan hal positif dan signifikan dalam meningkatkan profesional guru untuk membantu guru dalam mengembangkan kompetensinya dalam merencanakan, melaksanakan, dan mengevaluasi pembelajaran; (2) Adanya motivasi dari kepala madrasah menjadi kekuatan guru untuk memiliki keinginan yang kuat dalam melaksanakan pekerjaan dengan semangat yang tinggi, maka upaya meningkatkan kompetensi profesional guru adalah meningkatkan motivasi kerja guru sehingga mampu meningkatkan kompetensi profesional guru. (3) Melalui program supervisi akademik oleh kepala madrasah, guru lebih profesional dalam mengajar sehingga peserta didik antusias untuk mengikuti pembelajaran karena kemampuan guru dalam menguasai materi pembelajaran dan mampu menghidupkan suasana belajar guru yang memiliki kompetensi profesional.